2002
DOI: 10.1177/194589240201600204
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Inflammation Associated with Contralateral Inverted Papilloma

Abstract: Unilateral IPs are associated with contralateral inflammation as detected by CT. This degree of contralateral inflammation is greater than that seen in other sinonasal tumors. The etiology of this association is unclear. A recent histological review suggested IP is an inflammatory polyp and not a true papilloma. Our data further suggest inflammation may be involved in the pathogenesis of IP. Further work is needed to better understand the pathophysiology and behavior of IP and to define its relationship to sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 9 publications
3
54
1
2
Order By: Relevance
“…Therefore, other risk factors, such as allergic rhinitis, smoking and occupation, which may predispose to sinonasal papilloma, were ignored. Chronic sinusitis is reported to occur in either side and inflammation is considered to be one of the causes of the sinonasal papilloma (Orlandi et al 2002;Orlandi 2010). However, this study showed a different tendency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, other risk factors, such as allergic rhinitis, smoking and occupation, which may predispose to sinonasal papilloma, were ignored. Chronic sinusitis is reported to occur in either side and inflammation is considered to be one of the causes of the sinonasal papilloma (Orlandi et al 2002;Orlandi 2010). However, this study showed a different tendency.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral inverted papilloma is associated with contralateral inflammation, and the degree of contralateral inflammation is greater than that seen in the other sinonasal tumors (Orlandi et al 2002). Inverted papilloma typically occurs within the ethmoid sinuses or near the ostium of the maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
“…This degree of contralateral inflammation is greater than that seen for other sinonasal tumours. 26 Inflammatory cells have been identified as a significant cell population in inverted papilloma, whereas they are less commonly encountered in other types of nasal polyps. 28 A histological review even suggested inverted papilloma to be an inflammatory polyp rather than a true papilloma.…”
Section: Common Presentationsmentioning
confidence: 99%
“…25 Chronic inflammation may be involved in the pathogenesis of inverted papilloma. 26,27 Unilateral inverted papilloma is associated with contralateral inflammation, as detected by computed tomography (CT). This degree of contralateral inflammation is greater than that seen for other sinonasal tumours.…”
Section: Common Presentationsmentioning
confidence: 99%
See 1 more Smart Citation